PRIMARY PACKAGING SELECTION AND VALUE ADDED ANALYSIS FOR BELEDANG FISH CRACKER - Nanang Sumiyarto; Evanila Silvia; Yessy Rosalina (BPFP Faperta UNIB, 2013)
The research objective is to examine the best materials of primary packaging for beledang fish crackers and measure its value added. The packaging used in the research are plastic PP (Polypropylene) with a thickness of 0.09 mm, rigid LDPE (Low Density Polyethylene) plastic with a thickness of 0.36 mm, OPP multilayer (Oriented Polypropylene) with a thickness of 0.06 mm, aluminum foil packaging with a thickness of 0.04 mm and plastic vacuum with a thickness of 0.02 mm. Respondents in the study were experts respondents consist of one academic person in food packaging subject, one practitioners in food industry (owners of the fish industry beledang chips) and three person of BPPOM practitioners in Bengkulu. The results showed that rigid LDPE plastic is considered to be the best packaging. The value-added on beledang fish crackers for using rigid LDPE plastic is 51504.48 USD / kg or increase of 49.05%.